2014
DOI: 10.3748/wjg.v20.i1.242
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic diagnosis of cervical esophageal heterotopic gastric mucosa with conventional and narrow-band images

Abstract: NBI endoscopy detects more cervical esophageal HGM than CI does. Fundic-type gastric mucosa constitutes the most common histology. One-fifth of patients have throat or dysphagic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
1
15
0
2
Order By: Relevance
“…NBI (figure 3) improves the detection of small lesions (54% vs 17%, p<0.0001 in a prospective study of 99 patients with CIP) 37. It is recommended to confidently rule out an inlet patch using virtual chromoendoscopy in light of this.…”
Section: Investigationmentioning
confidence: 99%
“…NBI (figure 3) improves the detection of small lesions (54% vs 17%, p<0.0001 in a prospective study of 99 patients with CIP) 37. It is recommended to confidently rule out an inlet patch using virtual chromoendoscopy in light of this.…”
Section: Investigationmentioning
confidence: 99%
“…In fact, two recently published studies from Taiwan and United Kingdom recommend HD-NBI as the standard technique for examination of the proximal oesophagus. Astonishingly, low general prevalences of 6.5 % [11] and 1.9 % [6], respective-ly, were found. Cheng et al [11] found significantly more smallsized HGMs using NBI, but low prevalence was found using both HDWL endoscopy (4.7 %) and the NBI mode (8.3 %), while other Asian studies found considerably higher prevalences of 13.8 % [9] and 21.0 % [8], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Astonishingly, low general prevalences of 6.5 % [11] and 1.9 % [6], respective-ly, were found. Cheng et al [11] found significantly more smallsized HGMs using NBI, but low prevalence was found using both HDWL endoscopy (4.7 %) and the NBI mode (8.3 %), while other Asian studies found considerably higher prevalences of 13.8 % [9] and 21.0 % [8], respectively. Factors that might have influenced detection rates, such as examination time (especially under non-blinded conditions), dose and type of sedation, or setting, were not considered in the recent studies, so that a bias in the results is possible.…”
Section: Introductionmentioning
confidence: 99%
“…The role of Hp in lammation in HGM is controversial; some studies in patients with a high frequency of bacteria [22,23] have shown a correlation between in lammation and the presence of H. pylori, but others [24,25] have not. Acid production and/or colonization of Hp in HGM patches can potentially lead to complications such as an esophageal ring, stenosis, ulcer, perforation or bleeding [26].…”
Section: Discussionmentioning
confidence: 99%